THE ROLE OF THE PROPROTEIN CONVERTASE SUBTILISIN / KEXIN TYPE 9 (PCSK9) IN THE PATHOPHYSIOLOGY OF ATHEROSCLEROSIS - Алексей Михайлович Чаулин; Артем Геннадьевич Александров; Ольга Сергеевна Александрова; Дмитрий Викторович Дупляков (Медицина в Кузбассе)
Increased serum low-density lipoprotein (LDL) concentrations are clearly the most important risk factors for cardiovascular diseases. Currently, statins are the most widely used drugs for treating patients with hypercholesterolemia, however, in some patients, the residual cardiovascular risk remains high even after the statin therapy is given with the maximum tolerated dose. A relatively recently discovered protein molecule, the proprotein convertase subtilisin / kexin type 9 (PCSK9), has become a new therapeutic target for lowering serum LDL levels. PCSK9 increases the degradation of low-density lipoprotein receptors (RLDL), which reduces the elimination of LDL particles from the bloodstream, leading to hyperlipidemia and the occurrence of atherosclerosis. In addition to the lipid effects, PCSK9 also has non-lipid functions, among which, the enhancement of inflammatory reactions is of greatest importance for the pathophysiology of atherosclerosis. The review also discusses the possibility of using PCSK9 as a diagnostic marker of cardiovascular diseases.